Comparison study of using different curing condition of tire powder - Abuluhoom, Waleed Mohamed Mohsen (2019)
Motorcar waste tyre has a steady increase in its generation annually in Malaysia. The number of motorcar waste tyres generated annually in the country was estimated to be 8.2 million or approximately 57,391 tons in the year 2006. In addition to this, 60% of the waste tyres are disposed via unknown routes. Waste tyres in Malaysia are neither categorized as solid waste or hazardous waste. Currently it is just generalized as trade waste. Since there isn’t any law or regulation which governs waste tyre management, we have decided to use this material. From the previvors studied it shows that Tire waste is non-environmentally friendly which consist of a complex structure. A structure that is unbreakable by nature normal reaction and unable to be recycled. This work determines the mechanical properties of concrete after partial sand replacement and compare the effect of using two types of concrete curing which are water curing and salt curing in compressive strength and flexural strength. The tyre waste used in this research is grinded into powder form and then used partially to replace sand in a concrete mix design to find its suitable percentage to be used to gain the optimum strength. The concrete cubes tested in this research are sized at (150mm x 150mm x 150mm) each and tested at different percentage of sand replacement. The cubes are casted at a 0% (controlled cube), 5% and 10%. Each percentage had 9 identical cubes casted to get an average data that was tested on the 7th and 28th day since it was casted. Moreover, for flexural test, 18 beams size 500mm x 100mm x 100mm Flexural strength decreased with increasing tyre rubber replacement. Eearly strength shows that salt curing produced concrete with higher compressive and flexural strength and the best result go for control.